Grasslands Stewards of East Africa: Voices of Pastoralists and Scientists - International Livestock Research Institute (International Livestock Research Institute, 2021)
Join experts from the International Livestock Research Institute (ILRI) including rangelands specialist Fiona Flintan, ecosystem ecologist Jason Sircely and gender scientist Renee Bullock to hear some ‘myth-busting’ facts about East Africa’s extraordinary drylands and dryland peoples, to discover why Africa’s rangelands are now in big transition, and to learn how we can best support local pastoral communities to continue their stewardship of these exceptional landscapes as they continually refine their adaptations to a changing physical, political and socio-economic climate. Hear directly from East African pastoralists Mary Letirok, a Samburu pastoralist, and Nickson ole Parmisa, a Masai livestock pastoralist and honorary wildlife warden in the Kitengela rangelands of Kenya. As agricultural ecologist Ian Scoones reminds us: ‘As we confront uncertainties in today’s complex and turbulent world, we could all learn from pastoralists, who continue to navigate uncertainties with deep knowledge and practised skill.’ This video was originally created for the Global Landscapes Forum on Drylands 3-4 June 2021.